2003
DOI: 10.1093/oxfordjournals.rpd.a006247
|View full text |Cite
|
Sign up to set email alerts
|

Norm workers: A challenge for internal dosimetry programmes

Abstract: The mining, milling and processing of uranium and thorium bearing minerals may result in radiation doses to workers. The control of occupational exposures from these natural sources of radiation imposes a challenge to regulators and radiation protection advisers. A survey pilot programme, which included six mines in Brazil and a monazite plant, was established, consisting of the collection and analysis of concentrations of uranium, thorium and polonium in urine, faeces and air samples. Results from workers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A 'blank' bioassay sample should be obtained from the workers prior to the commencement of work. When not possible, bioassay samples from family members or from the population living in the same area should be taken and analysed to allow natural or non-occupational intakes and occupational intakes to be distinguished (Eckerman and Kerr, 1999;Lipsztein et al, 2001Lipsztein et al, , 2003. It may be useful to use this information to define a level above which occupational exposure is indicated.…”
Section: Influence Of Backgroundmentioning
confidence: 99%
“…A 'blank' bioassay sample should be obtained from the workers prior to the commencement of work. When not possible, bioassay samples from family members or from the population living in the same area should be taken and analysed to allow natural or non-occupational intakes and occupational intakes to be distinguished (Eckerman and Kerr, 1999;Lipsztein et al, 2001Lipsztein et al, , 2003. It may be useful to use this information to define a level above which occupational exposure is indicated.…”
Section: Influence Of Backgroundmentioning
confidence: 99%
“…Dalheimer et al [ 8 ] recently reported a daily urinary excretion median value of 3.5 mBq d −1 for non-smokers and 6.6 mBq d −1 for smokers. In Brazil, the reported values of 210 Po excretion in urine were 5.2 mBq l −1 for non-smokers and 9.8 mBq l −1 for smokers [ 9 , 10 ]. In Saudi Arabia, the measured values range from 1.5 to 10 mBq l −1 for non-smokers and 3.3 to 15.9 mBq l −1 for smokers [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 819 natural background level measurements, almost 550 measurements were extracted from studies reported in the literature (Black 1956, Radford and Hunt 1964, Taylor et al 1964, Glöbel et al 1966, Kuroda 1967, Holgye 1969, De Boeck et al 1971, Ladinskaya et al 1973, Bale et al 1975, Eakins and Morrison 1975, Novakova et al 1975, Okabayashi et al 1975, Juan and Ballelos 1976, Holtzman et al 1971, 1979, Spencer et al 1977, Helmkamp et al 1979, Clemente et al 1980, Okabayashi 1982, Irlweck 1982, Mancini et al 1984, Fenzi 1986, Azeredo and Lipsztein 1991, Hunt and Allington 1993, Santos et al 1994, 1995, 2000, Naumann et al 1998, Thomas et al 2001, Lipsztein et al 2003, Samavat and Seaward 2004, Schafer et al 2005, Al-Arifi et al 2006, Hunt and Rumney 2007, Kirchner and Kröger 2008, Gjelsvik et al 2009, Puerta et al 2009, Manickam et al 2010, Gascó et al 2011. The additional 269 measurements were contributions of previously unpublished data.…”
Section: Review Of Datamentioning
confidence: 99%